The multi-level regulation of clownfish metamorphosis by thyroid hormones - Natacha Roux; Saori Miura; Mélanie Dussenne; Yuki Tara; Shu-hua Lee; Simon de Bernard; Mathieu Reynaud; Pauline Salis; Agneesh Barua; Abdelhay Boulahtouf; Patrick Balaguer; Karine Gauthier; et al. (Cell Reports, 2023)
Summary: Most marine organisms have a biphasic life cycle during which pelagic larvae transform into radically different juveniles. In vertebrates, the role of thyroid hormones (THs) in triggering this transition is well known, but how the morphological and physiological changes are integrated in a coherent way with the ecological transition remains poorly explored. To gain insight into this question, we performed an integrated analysis of metamorphosis of a marine teleost, the false clownfish (Amphiprion ocellaris). We show how THs coordinate a change in color vision as well as a major metabolic shift in energy production, highlighting how it orchestrates this transformation. By manipulating the activity of liver X regulator (LXR), a major regulator of metabolism, we also identify a tight link between metabolic changes and metamorphosis progression. Strikingly, we observed that these regulations are at play in the wild, explaining how hormones coordinate energy needs with available resources during the life cycle.